STUDI KOMPARATIF PEMIKIRAN JOHN RAWLS DAN MARTHA NUSSBAUM TENTANG KEADILAN SOSIAL - Indah, Astrid Veranita; Siola, Muhammad Natsir (Prodi Aqidah dan Filsafat Islam Fakultas Ushuluddin dan Filsafat UIN Alauddin Makassar, 2025)
This research examines the philosophical thoughts of John Rawls and Martha Nussbaum on social justice through library research methods with a qualitative hermeneutic approach. The primary focus is to explore the concept of justice from both thinkers' perspectives, analyze convergence and divergence points, and synthesize a comprehensive conceptual framework. The study compares four key domains: equality conception, resource distribution mechanisms, the state's role, and the ethical dimensions of social life. Research findings demonstrate that social justice is a dynamic practice that transcends material distribution, emphasizing individual empowerment and human dignity recognition. Rawls offers a procedural approach through the original position, while Nussbaum focuses on core capabilities development. The synthesis of their thoughts produces a theoretical framework that promotes public policy transformation towards a more inclusive and just society.